Production and optimisation of used cooking palm oil into protected fat calcium salts by fusion method using response surface methodology (RSM) - Mohamad Asrol, Kalam; Pak Dek, Mohd Sabri; Suyub, I. B.; Sugnaseelan, Sumita; Jusoh, Shokri (Universiti Putra Malaysia, 2023)
Used cooking oil (UCO) is a waste, and creates environmental issues due to its hydrophobic property. UCO, with its high content of fatty acid, can be used as source material for animal feed. However, high unsaturated fatty acid in UCO is harmful to the ruminant’s microflora. This can be resolved by transforming UCO into functional product such as ruminant’s protected fat (PF). In the present work, the production of used cooking oil protected fat (UCOPF) using fusion method via saponification process was investigated. Response surface methodology (RSM) was used to evaluate the effect of calcium oxide concentration (CaO), initial temperature (iTemp.), and percentage of water (H2O) on the solidification score and free fatty acid (FFA) content of PF. Results showed that all the studied parameters significantly affected the responses. The coefficient of determination (R2) for solidification score and FFA were high at 0.9433 and 0.9599, respectively. The optimum condition to produced UCOPF by fusion method was CaO (20%), iTemp. (80°C), and percentage of water (30%), which yielded solidification score and FFA of 5.33 ± 0.53 and 0.85 ± 0.07%, respectively. The FFA content of the optimised PF was lower than permitted; thus, it can be used as animal supplement. In conclusion, the UCO can be converted into PF by using calcium fusion method. However, the property and stability of the produced PF should be assessed prior to commercialisation.